Understanding cross-cultural psychology Eastern and Western perspectives - Laungani, Pittu; Sage eBooks (London : SAGE, 2007)
'Cross-Cultural Psychology' provides a solid and interesting foundation for any undergraduate student with an interest in the cross-cultural aspects of psychology.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Ethnopsychology; Cross-cultural orientation; Electronic books